Engineered CAR-Macrophages as Adoptive Immunotherapies for Solid Tumors - Sloas, Christopher; Gill, Saar; Klichinsky, Michael (Frontiers in Immunology, 2021)
Cellular immunotherapies represent a promising approach for the treatment of cancer. Engineered adoptive cell therapies redirect and augment a leukocyte’s inherent ability to mount an immune response by introducing novel anti-tumor capabilities and targeting moieties. A prominent example of this approach is the use of T cells engineered to express chimeric antigen receptors (CARs), which have demonstrated significant efficacy against some hematologic malignancies. Despite increasingly sophisticated strategies to harness immune cell function, efficacy against solid tumors has remained elusive for adoptive cell therapies. Amongst cell types used in immunotherapies, however, macrophages have recently emerged as prominent candidates for the treatment of solid tumors. In this review, we discuss the use of monocytes and macrophages as adoptive cell therapies. Macrophages are innate immune cells that are intrinsically equipped with broad therapeutic effector functions, including active trafficking to tumor sites, direct tumor phagocytosis, activation of the tumor microenvironment and professional antigen presentation. We focus on engineering strategies for manipulating macrophages, with a specific focus on CAR macrophages (CAR-M). We highlight CAR design for macrophages, the production of CAR-M for adoptive cell transfer, and clinical considerations for their use in treating solid malignancies. We then outline recent progress and results in applying CAR-M as immunotherapies. The recent development of engineered macrophage-based therapies holds promise as a key weapon in the immune cell therapy armamentarium.